Effects of Neutrophil-to-Lymphocyte Ratio Combined With Interleukin-6 in Predicting 28-Day Mortality in Patients With Sepsis - Liu, Shuangqing; Wang, Xinkun; She, Fei; Zhang, Wei; Liu, Hongsheng; Zhao, Xiaodong (Frontiers in Immunology, 2021)
Background: The current study aimed to evaluate the relationship between the neutrophil-to-lymphocyte ratio (NLR) combined with interleukin (IL)-6 on admission day and the 28-day mortality of septic patients. Material and Methods: We conducted an observational retrospective study. Patients with presumed sepsis were included. We observed the correlation of studied biomarkers (NLR, IL-6, PCT and CRP) and the severity scores (APACHE Ⅱ and SOFA scores) by plotting scatter plots. The relationships of studied biomarkers and 28-day mortality were evaluated by using Cox regression model, receiver-operating characteristic (ROC) curve, and reclassification analysis. Results: A total of 264 patients diagnosed with sepsis were enrolled. It was revealed that IL-6 had the strongest correlation with both APACHE Ⅱ and SOFA scores, followed by the NLR and PCT, and there was no obvious correlation between CRP and the illness severity. NLR and IL-6 were independent predictors of the 28-day mortality in septic patients in the Cox regression model (NLR, odds ratio 1.281 [95% CI 1.159-1.414], P<0.001; IL-6, odds ratio 1.017 [95% CI 1.005-1.028], P=0.004). The area under the ROC curve (AUC) of NLR, IL-6 and NLR plus IL-6 (NLR_IL-6) was 0.776, 0.849 and 0.904, respectively. Conclusion: Our study showed that the levels of NLR and IL-6 were significant higher in the deceased patients with sepsis. NLR and IL-6 appeared to be independent predictors of 28-day mortality in septic patients. Moreover, NLR combined with IL-6 could dramatically enhance the prediction value of 28-day mortality.